KHALED M. ABOU El-FADL’S AUTHORITATIVE HERMENEUTICS: AGAINST AUTHORITARIANISM IN ISLAMIC LAW - Juliansyahzen, Muhammad Iqbal (Universitas Islam Indonesia, 2019)
Authoritarianism stems from an imbalance between text, author, and reader. The relationship between those three elements must occur dialectically-dynamically. Khaled M. Abou El Fadl scrutinized religious fatwas of fatwa institutions in Saudi Arabia that tend to discriminate against women to prove the existence of authoritarianism in Islamic legal thought. Abou El Fadl stressed the importance of referring to authoritative sources as an embodiment of authoritative law. For him, the Qur’an is the main authoritative source that is no doubt. In contrast, the traditions (Hadith) need further proof, considering the codification of the hadith took place two centuries after the death of the Prophet. Abou El Fadl built his concept of authority based on Friedman’s thinking which distinguishes coercive authority from persuasive authority. He also distinguished between holding authority and assuming authority. The difference between the two will lead to different legal consequences. Based on this, Abou El Fadl offered authoritative hermeneutics as a methodological framework.